RESPONS MAHASISWA TERHADAP WEBSITE PURNAMA JAYA FARM SLEMAN - , GHANI PRADITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to identify creation of Purnama Jaya Farmâs website, knowing the response of students toward the website, and the influencing factors of it. The method used in this research was descriptive approach by survey technique. The sampling of department were done purposively, while the sampling of students was done randomly. The number of total sample was 64 students from Department of Agricultural Socio-Economics from class of 2010 to class of 2013. From each class taken 8 Agribusiness students and 8 Agricultural Extension and Communication students. The analysis methods used proportion test and multiple linier regression analysis. The result of this research showed that response of students toward Purnama Jaya Farmâs website were high. The quality of information and ease of use positively affected toward response of students, while sex, academic program, degree of education, perception, quality of system, and playfulness didnât have significant affect.